Systematics of Hyperolius mitchelli Loveridge, 1953 and Hyperolius rubrovermiculatus Schiøtz, 1975 (Anura: Hyperoliidae) and assignment of populations from northern Tanzania. Issue 2 (2nd July 2020) - Bwong, Beryl A; Barratt, Christopher D; Loader, Simon P; Nyamache, Joash O; Menegon, Michele; Malonza, Patrick K; Nagel, Peter; Lawson, Lucinda P
ABSTRACT : The taxonomic validity of the East African reed frogs Hyperolius mitchelli Loveridge, 1953 and Hyperolius rubrovermiculatus Schiøtz, 1975 has been questioned in the literature, with the latter having been recognised as a distinct lineage, but also synonymised as a colour variant of H. mitchelli . The recent description of a new closely related congener from Mozambique, Hyperolius stictus (Conradie et al., 2018 ), along with evidence of genetic differentiation within H. mitchelli has suggested that this widely distributed species might be a species complex. In this study, we reassess the relationships of these closely related species with new field sampling, molecular, morphological and bioacoustics analyses with the aim to assign the correct taxonomic identity to H . cf. mitchelli from northern Tanzania. Our results demonstrate that there are four distinct lineages within this group: H. stictus from Mozambique; H. rubrovermiculatus from southern Kenya; H. mitchelli sensu stricto from central and southern Tanzania and Malawi and H . cf. mitchelli from north-eastern Tanzania. Based on our combined analyses we assign H . cf. mitchelli as a new population of H. rubrovermiculatus with distinct colouration, extending the range of this species from Kenya into northern Tanzania. We also clarify the genetic, morphological and acoustic variation within and between all lineages to further knowledge of this group and provide direction for future study into this fragmented and variable lineage.